Viral disease emergence in shrimp aquaculture: origins, impact and the effectiveness of health management strategies - Peter J. Walker; C. V. Mohan (Reviews in Aquaculture, 2009)
Shrimp aquaculture has grown rapidly over several decades to become a major global industry that serves the increasing consumer demand for seafood and has contributed significantly to socio‐economic development in many poor coastal communities. However, the ecological disturbances and changes in patterns of trade associated with the development of shrimp farming have presented many of the pre‐conditions for the emergence and spread of disease. Shrimp are displaced from their natural environments, provided artificial or alternative feeds, stocked in high density, exposed to stress through changes in water quality and are transported nationally and internationally, either live or as frozen product. These practices have provided opportunities for increased pathogenicity of existing infections, exposure to new pathogens, and the rapid transmission and transboundary spread of disease. Not surprisingly, a succession of new viral diseases has devastated the production and livelihoods of farmers and their sustaining communities. This review examines the major viral pathogens of farmed shrimp, the likely reasons for their emergence and spread, and the consequences for the structure and operation of the shrimp farming industry. In addition, this review discusses the health management strategies that have been introduced to combat the major pathogens and the reasons that disease continues to have an impact, particularly on poor, small‐holder farmers in Asia.